Dietary Supplement of Anoectochilus roxburghii (Wall.) Lindl. Polysaccharides Ameliorates Cognitive Dysfunction Induced by High Fat Diet via “Gut-Brain” Axis - Fu L; Zhu W; Tian D; Tang Y; Ye Y; Wei Q; Zhang C; Qiu W; Qin D; Yang X; Huang Y (Dove Medical Press, 2022)
Liya Fu,1,2,* Wanlong Zhu,1,2,* Dongmei Tian,1,2 Yong Tang,2,3 Yun Ye,1 Qiming Wei,1 Chengbin Zhang,1 Wenqiao Qiu,2 Dalian Qin,2 Xuping Yang,1,2 Yilan Huang1,2 1Department of Pharmacy, The Affiliated Hospital of Southwest Medical University, Luzhou, People's Republic of China; 2School of Pharmacy, Southwest Medical University, Luzhou, People's Republic of China; 3State Key Laboratory of Quality Research in Chinese Medicine, Macau University of Science and Technology, Macau, 999078, People's Republic of China*These authors contributed equally to this workCorrespondence: Xuping Yang; Yilan Huang, Department of Pharmacy, The Affiliated Hospital of Southwest Medical University, Luzhou, People's Republic of China, Email yangxuping6552@163.com; lzyxyyxp123@163.comPurpose: Anoectochilus roxburghii (Wall.) Lindl. polysaccharides (ARPs) have been reported to exhibit multiple pharmacological activities including anti-inflammatory and anti-hyperglycemia. This study aims to investigate the effect of ARPs on cognitive dysfunction induced by high fat diet (HFD).Methods: Six-week-old male mice were treated with ARPs by dietary supplementation for 14 weeks. The effect of ARPs on cognitive function was determined by assessing the changes in spatial learning and memory ability, neurotrophic factors in hippocampus, inflammatory parameters, intestinal barrier integrity, and gut microbiota.Results: ARPs supplementation can effectively ameliorate cognitive dysfunction, decrease the phosphorylation levels of Tau protein in hippocampus. Meanwhile, the increased body weight, plasma glucose, total cholesterol, inflammatory factors induced by HFD were abolished by ARPs treatment. Furthermore, ARPs treatment restored the intestinal epithelial barrier as evidenced by upregulation of intestinal tight junction proteins. Additionally, ARPs supplementation significantly decreased the relative abundance of several bacteria genus such as Parabacteroides, which may play regulatory roles in cognitive function.Conclusion: These results suggest that ARPs might be a promising strategy for the treatment of cognitive dysfunction induced by HFD. Mechanistically, alleviation of cognitive dysfunction by ARPs might be associated with the "gut-brain" axis.Graphical Abstract: Keywords: Anoectochilus roxburghii (Wall.) Lindl. polysaccharides, diet-induced-obesity, cognitive dysfunction, gut microbiota, "gut-brain" axis